Hubungan Perbedaan Ketinggian dengan Perubahan Tekanan Darah pada Pelaku Perjalanan dari Dataran Rendah ke Dataran Tinggi dan dari Dataran Tinggi ke Dataran Rendah - Fernando P. Salipadang; Vennetia R. Danes; Maya E. W Moningka (eBiomedik, 2022)
Abstract: The effect of altitude differences to blood pressure changes in someone is known to give various results, where an increase or decrease of altitude will also make an increase or decrease in blood pressure proportionally, or no changes in blood pressure. The most important process that correlate to this blood pressure changes is due to the activation of the autonomic nervous system as a result of the acclimatization. This study was aimed to determine whether the relationship between altitude differences and blood pressure changes among the travelers who traveled from low altitude to high altitude and vice versa. This study is an analytical observational with cross sectional design, involving 50 respondents who have met the inclusion criterias, divided into two groups who traveled from the city of Manado to Tomohon (low to high altitude area) and from the city of Tomohon to Manado (high to low altitude area) and then, the systolic and diastolic and blood pressure was measured in both treatment groups. Then statistical correlation test and hypothesis test of significance were analyzed with SPSS version 25. Based on the statistical correlation test (Pearson product and Kendall's Tau) and hypothesis test of significance (paired T-test and Wilcoxon test), the correlation coefficients and significances of hypothesis tests between the differences in altitude (Manado to Tomohon city and Tomohon to Manado city) and changes in systolic and diastolic blood pressure are  = 0.897, p = 0.000 < 0.05 and = 0.779, p = 0.048 < 0.05 and  = 0.890, p = 0.003 < 0.05 and  = 0.907, p = 0.024< 0.05. (significant if p<0.05, with = 0.05). In conclusion, There is a linear, real and significant relationship between changes in altitude, from low to high altitude area, vice versa and changes in systolic and diastolic blood pressure.Keywords: Altitude; low altitude; high altitude; blood pressure; systolic blood pressure; diastolic blood pressure  Abstrak: Pengaruh perbedaan ketinggian/ altitude seseorang terhadap perubahan tekanan darah diketahui memberikan hasil yang beragam, dimana peningkatan atau penurunan ketinggian juga akan berbanding terhadap peningkatan atau penurunan tekanan darah, yang terpenting dikarenakan adanya aktivasi sistem saraf otonom sebagai akibat adanya proses aklimatisasi. Penelitian ini dilakukan untuk mengetahui hubungan perbedaan ketinggian terhadap tekanan darah pada pelaku perjalanan dari dataran rendah ke dataran tinggi dan sebaliknya. Penelitan ini bersifat observasional analitik secara cross sectional, melibatkan 50 responden yang telah memenuhi kriteria inklusi, terbagi dalam dua kelompok yang melakukan perjalanan dari kota Manado ke  kota Tomohon (dataran rendah ke dataran tinggi) dan dari kota Tomohon ke Manado (dataran tinggi ke dataran rendah ) dan dilakukan pengukuran tekanan darah sistolik dan diastolik pada kedua kelompok perlakuan tersebut. Kemudian dilakukan analisis statistik korelasi serta uji hipotesis dengan bantuan SPSS vers. 25. Berdasarkan uji statistik korelasi (Pearson product dan Kendall’s Tau) dan uji hipotesis (uji T-berpasangan dan Uji Wilcoxon), secara berturut- turut koefisien korelasi dan signifikansi uji hipotesis antara perbedaan ketinggian (kota Manado ke Tomohon dan sebaliknya) terhadap perubahan tekanan darah sistolik dan diastolik sebesar =0,897, p =0,000< 0,05 dan  = 0,779, p=0,048< 0,05 serta  =0,890, p =0,003< 0,05 dan  =0,907, p =0,024< 0,05. (signifikan apabila p<0,05, dengan  = 0,05). Sebagai simpulan, terdapat hubungan yang searah, nyata dan bermakna antara perbedaan ketinggian, baik dari dataran rendah ke dataran tinggi dan sebaliknya terhadap perubahan tekanan darah sistolik dan diastolik.Kata kunci: ketinggian; dataran rendah; dataran tinggi; tekanan darah; tekanan darah sistolik; tekanan darah diastolik